2022
DOI: 10.1002/smm2.1098
|View full text |Cite
|
Sign up to set email alerts
|

Organic frameworks confined Cu single atoms and nanoclusters for tandem electrocatalytic CO2 reduction to methane

Abstract: The electrochemical reduction reaction of carbon dioxide (CO2RR) is considered to be an effective way to realize carbon neutrality. As a type of intensively studied materials, covalent organic frameworks (COFs) with a tunable pore structure and various functional groups are promising catalysts for CO2RR. Herein, COF synthesized by 2,6‐diaminoanthraquinone and 2,4,6‐triformylphloroglucinol is employed to assist the synthesis of electrocatalysts from Cu single atoms (SAs) to nanoclusters by controlling the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…First, Fe SAS/Tr-COF photocatalysts with atomically dispersed Fe atoms can expose abundant metal active sites to effectively capture CO 2 molecules. Second, the formed Fe–N charge bridge in Fe SAS/Tr-COFs can provide an additional channel for further ultra-fast electron migration from Tr-COF units to atomically dispersed Fe centers, thus achieving the long-life carrier separation. , Third, the absorbed CO 2 could be effectively reduced to the CO product on the Fe SAS/Tr-COF catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…First, Fe SAS/Tr-COF photocatalysts with atomically dispersed Fe atoms can expose abundant metal active sites to effectively capture CO 2 molecules. Second, the formed Fe–N charge bridge in Fe SAS/Tr-COFs can provide an additional channel for further ultra-fast electron migration from Tr-COF units to atomically dispersed Fe centers, thus achieving the long-life carrier separation. , Third, the absorbed CO 2 could be effectively reduced to the CO product on the Fe SAS/Tr-COF catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The high‐magnification HAADF‐STEM images can more intuitively display the dispersion of metal atoms on the carrier. [ 12 ] The Pt atoms of Pt‐SA@HG were corroborated to be uniformly dispersed on the carrier with isolated bright dots (Figure 1e). However, in samples Pt‐Clu@HG and Pt‐Nc@HG, Pt elements have obvious aggregation (Figure 1f,g, Figures S4 and S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
“…Recently, Shao and co-workers prepared Cu single atoms (SAs) to nanoclusters (NCs) electrocatalysts confined by a conductive 2D COF structure by electrodeposition. [182] The resulting NCs-SAs Cu/COF electrocatalyst exhibited the highest FE CH4 (56.2% � 5%) at the potential of À 1.26 V vs. RHE. They found that the electrodeposited Cu NCs were distributed around the Cu SAs.…”
Section: Cu-based Cof Compositesmentioning
confidence: 93%
“…With the changes of the working potentials, the Cu clusters depolymerized into Cu 2+ and most of the stripped Cu 2+ was re‐anchored by CTF−B due to the strong Cu‐bipyridine interaction, thus reforming the CTF−Cu structure. Recently, Shao and co‐workers prepared Cu single atoms (SAs) to nanoclusters (NCs) electrocatalysts confined by a conductive 2D COF structure by electrodeposition [182] . The resulting NCs‐SAs Cu/COF electrocatalyst exhibited the highest FE CH4 (56.2% ±5%) at the potential of −1.26 V vs. RHE.…”
Section: Cu‐based Organic‐inorganic Compositesmentioning
confidence: 99%